PENGARUH WORD OF MOUTH, BRAND AWARENESS, DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN YOGA MAT DI UNIQUE YOGA SHOP BALI - Ni Made Ayu Oka Dewi; Ni Putu Nita Anggraeni; I Wayan Gede Antok Setiawan Jodi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
The development of communication in the marketing strategy has an important role for business actors in influencing a consumer purchasing decision. The increasing public interest in doing yoga, of course, influences the decision to purchase a yoga mat at Unique Yoga Shop Bali as one of the distributors of yoga products in Bali. So that there is an increase in sales of its main product, namely yoga mat, which is believed to be influenced by Word of Mouth, Brand Awareness, and Social Media Marketing factors on the decision to buy yoga mat at Unique Yoga Shop Bali. The population of this study are other people who have bought yoga mats at Unique Yoga Shop Bali, the exact number of which is unknown. The sample in this study was determined based on the purposive sampling method using the Hair formula as many as 126 respondents.The results of the study show that Word of Mouth, Brand Awareness, and Social Media Marketing have a positive and significant effect on the decision to purchase yoga mat at Unique Yoga Shop Bali. Suggestions for further research can develop this research by adding other variables.